Preventing Attacks on the Easiest Applications with Vulnerabilities by Verification of Their Committed System Calls - M. A. Parinov; A. G. Sirotkina (Глобальная ядерная безопасность)
The issue of detecting and preventing attacks on applications has been and remains one of the urgent tasks of information security. Flaws in the program code lead to disruption of the normal operation of the software. Data integrity, availability and confidentiality of the data, interruption of the execution of running processes or even the system as a whole may occur due to design flaws. The aim of this work is to prevent attacks on the application by overflowing the buffer using the developed complex to prevent attacks. To achieve this goal, the shortcomings of modern systems for preventing attacks on applications are briefly reviewed, the structure of the developed software package, the operation algorithms of each module of the software package, the mechanism for buffer overflows are examined, and the developed software package is tested on a simple buffer overflow.